Intra-articular Basic Calcium Phosphate and Monosodium Urate Crystals Inhibit anti-osteoclastogenic Cytokine Signalling - Dunne, Aisling; Cunningham, C.C.; Corr, E.M.; McCarthy, G.M. (My University, 2016)
Objective: Basic calcium phosphate (BCP) and monosodium urate (MSU) crystals are particulates with potent pro-inflammatory effects, associated with osteoarthritis (OA) and gout, respectively. Bone erosion, due to increased osteoclastogenesis, is a hallmark of both arthropathies and results in severe joint destruction. The aim of this study was to investigate the effect of these endogenous particulates on antiosteoclastogenic cytokine signalling. Methods: Human osteoclast precursors (OcP) were treated with BCP and MSU crystals prior to stimulation with Interleukin (IL-6) or Interferon (IFN-g) and the effect on Signal Transducer and Activator of Transcription (STAT)-3 and STAT-1 activation in addition to Mitogen Activated Protein Kinase (MAPK) activation was examined by immunoblotting. Crystal-induced suppressor of cytokine signalling (SOCS) protein and SH-2 containing tyrosine phosphatase (SHP) expression was assessed by real-time polymerase chain reaction (PCR) in the presence and absence of MAPK inhibitors. Results: Pre-treatment with BCP or MSU crystals for 1 h inhibited IL-6-induced STAT-3 activation in human OcP, while pre-treatment for 3 h inhibited IFN-g-induced STAT-1 activation. Both crystals activated p38 and extracellular signaleregulated (ERK) MAPKs with BCP crystals also activating c-Jun N-terminal kinase (JNK). Inhibition of p38 counteracted the inhibitory effect of BCP and MSU crystals and restored STAT-3 phosphorylation. In contrast, STAT-1 phosphorylation was not restored by MAPK inhibition. Finally, both crystals potently induced the expression of SOCS-3 in a MAPK dependent manner, while BCP crystals also induced expression of SHP-1 and SHP-2. Conclusion: This study provides further insight into the pathogenic effects of endogenous particulates in joint arthropathies and demonstrates how they may contribute to bone erosion via the inhibition of antiosteoclastogenic cytokine signalling. Potential targets to overcome these effects include p38 MAPK, SOCS-3 and SHP phosphatases.
PUBLISHED
Keywords: Osteoclasts; Crystal deposition disease; Osteoarthritis; Gout; Immunology, Inflammation & Infection; Autoimmune Diseases (Multiple Sclerosis, Rheumatoid Arthritis); Chronic Health Condition; Health